Pengembangan Desa Wisata Berbasis Ekonomi Kreatif Masyarakat Desa Lubuk Beringin Kabupaten Bungo - A A Musyaffa; Muhammad Fajar Maulana; Ridho Herman Saputra; Astuti Nurhidayah; Eko Wahyudi; Nur Aisyahni; Rahmat Ilahi (Indonesian Journal of Community Services, 2022)
The regular KKN program in 2022 in Lubuk Beringin Village wants to try to develop existing tourist villages by conducting several initiation programs as the beginning of the development of tourism villages. Several things are done to optimize natural tourism villages, especially household products in Lubuk Beringin Village. The results of activities in supporting the development of tourism villages in Lubuk Beringin such as nature tourism, culinary tourism, herbal tourism, and also souvenir centers. The programs carried out recently are initiation programs so it is necessary to optimize every aspect of support so that the Lubuk Beringin tourism village program becomes a tourist attraction that is in demand by domestic and foreign tourists. The initiation programs that have been carried out in Lubuk Beringin are Human Resources Training in English Practise, Training Training, and direct practice of digital marketing Interpreuner Training (Training in making dishes and culinary). The results of the implementation of the program received the enthusiasm of the residents and this is a positive start so there will be a development of a tourist village in Lubuk Beringin Village.